Peptide Bond Formation in the Protonated Serine Dimer Following Vacuum UV Photon‐Induced Excitation. (3rd March 2023) - Licht, Ori; Barreiro‐Lage, Darío; Rousseau, Patrick; Giuliani, Alexandre; Milosavljević, Aleksandar R.; Isaak, Avinoam; Mastai, Yitzhak; Albeck, Amnon; Singh, Raj; Nguyen, Vy T. T.; Nahon, Laurent; Martínez‐Fernández, Lara; et al.
Abstract: Possible routes for intra‐cluster bond formation (ICBF) in protonated serine dimers have been studied. We found no evidence of ICBF following low energy collision‐induced dissociation (in correspondence with previous works), however, we do observe clear evidence for ICBF following photon absorption in the 4.6–14 eV range. Moreover, the comparison of photon‐induced dissociation measurements of the protonated serine dimer to those of a protonated serine dipeptide provides evidence that ICBF, in this case, involves peptide bond formation (PBF). The experimental results are supported by ab initio molecular dynamics and exploration of several excited state potential energy surfaces, unraveling a pathway for PBF following photon absorption. The combination of experiments and theory provides insight into the PBF mechanisms in clusters of amino acids, and reveals the importance of electronic excited states reached upon UV/VUV light excitation. Abstract : While collision induced dissociation of protonated serine dimers leads only to cluster breakup, clear evidence that irradiation by Vacuum UV (PID) light leads to intra‐cluster bond formation is presented. Furthermore, comparison with the PID of serine dipeptides suggests that peptide bond formation is involved in the process.